(untitled) (Journal of Information Technology and Digital World, 2024)
It has been shown in recent years that the safe interchange of medical data improves people’s care and treatment, thereby enhancing their quality of life. Blockchain technology has the power to revolutionize healthcare management systems by improving data security, interoperability, and integrity, thanks to its decentralized and unchangeable structure. As an emerging option for achieving balance in the healthcare ecosystem, blockchain technology facilitates interoperability between diverse healthcare systems through the use of smart contracts and standardized data formats. Despite its potential advantages, interoperability remains an ongoing challenge in the healthcare environment. From an architectural perspective, trade-offs must be considered in the design of a blockchain-based system. However, obstacles such as user acceptance, scalability issues, and regulatory compliance impede the implementation of blockchain in the healthcare industry. This study provides valuable insights into the evolving landscape of healthcare data management by highlighting the potential advantages and challenges associated with integrating blockchain technology into healthcare management systems. Additionally, it suggests a Blockchain-based electronic healthcare management (EHR) model that could address some of the limitations of the existing systems. Keywords: Decentralization, Security, Blockchain, Electronic Health Record, Health Care Management